From Chinese brand culture to global brands : insights from aesthetics, fashion, and history - Zhiyan, Wu. (Palgrave Macmillan, 2013)
"An insightful exploration of the global growth of Chinese brands that presents a unique Chinese perspective on history and culture in branding. China's growing economic power is an established fact, but why have Chinese brands so far been unable to translate success at home to international recognition? Including case studies such as: the 2008 Beijing Olympics opening ceremony, arguably the most expensive branding effort in recent memory; and Shanghai Tang, a global fashion brand with aesthetic roots in Chinese historical culture, From Chinese Brand Culture to Global Brands is an expert and insightful look at Chinese brand culture and its capacity to serve as a complement to existing models of brand globalization. Rather than explore Western branding in Chinese contexts, this book shows how some successful Chinese brands that are reaching a global audience build upon significant aspects of Chinese culture and history. From Chinese Brand Culture to Global Brands examines how Chinese brands are perceived both internationally and in China, and argues that branding strategy that draws upon a more self-consciously Chinese aesthetic would leave Chinese brand culture poised for global success. "--